Responding to conflict in Africa : the United Nations and regional organizations - Boulden, Jane, 1962- (New York, NY : Palgrave Macmillan, 2013)
"Africa has been the source of some of the international community's most devastating failures and important successes in conflict management. The purpose of this book is to examine the issues and experiences associated with the increased level of activity between the United Nations and regional organizations in their efforts to address conflict in Africa. Using nine case studies and an overview of recent changes at the institutional level this book assesses what these experiences tell us about the United Nations, about African regional organizations, and about conflict management processes."--Publisher's website.
Introduction / Jane Boulden -- Part 1 : The UN and African regional organizations -- The United Nations Security Council and conflict in Africa / Jane Boulden -- The African Union / Thomas Kwasi Tieku -- The peace and security architecture of African sub-regional organizations / Anthoni van Nieuwkerk -- Sanctions and Africa : UN and regional responses / Andrea Charron -- Part 2 : Case studies. -- Burundi, 2002-2012 / Gilbert M. Khadiagala -- Chad and the Central African Republic / Arthur Boutellis -- r
Includes bibliographical references and indexes.
Keywords: United Nations -- Peacekeeping forces -- Africa; United Nations; Conflict management -- Africa; Regionalism (International organization); Prévention des conflits; Maintien de la paix; Organisation des Nations unies; Organisations africaines; Etudes de cas; Politique internationale; Conflict management; Peacekeeping forces; Regionalism (International organization); Friedenssicherung; Afrique; Africa